Efficiency and Stability of Transarterial Chemoembolization Combined With or Without Lenvatinib for Unresectable Hepatocellular Carcinoma - Zong, Zheng; Tang, Rongyu; Li, Mingyu; Xiong, Xinmiao; li, Daixin; Fan, Jing; Ye, Wei; Xue, Chenqi (Turkish Journal of Gastroenterology, 2024)
Background/Aims: At present, there are relatively few reports on the treatment consisting of transarterial chemoembolization (TACE) combined with lenvatinib, and there is no unified conclusion on the curative effect. The objective of this research was to assess the efficacy and safety of combining TACE with lenvatinib for the treatment of unresectable hepatocellular carcinoma (uHCC). Materials and Methods: This study was a retrospective analysis of the patients medical records. In this study, 249 patients (uHCC) in our hospital from 2020 to 2021 were divided into 2 groups, including the TACE-alone group (198 patients received TACE alone) and the TACE-LEN group (51 patients were treated with TACE combined with lenvatinib). According to the propensity score matching method, there were TACE-LEN group (51 patients) and TACE-alone group (51 patients). With the help of surgical experts, the overall survival (OS), progression-free survival (PFS), and tumor response (according to mRECIST) of the 2 groups were sorted and recorded, and then analyzed. Survival curves were established, the prognostic factors of OS and PFS were analyzed by univariate and multivariate analyses, and the independent prognostic factors were recorded. The adverse reactions of patients after treatment were recorded. Results: The 1-year and 2-year OS rates were 50.98% and 19.48% for the TACE-LEN group, 27.45% and 8.55% for the TACE-alone group (P = .042), respectively. The PFS of patients in the TACE-LEN group was also longer (1-year PFS rate: 25.49% vs. 11.76%, 2-year PFS rate: 19.17% vs. 5.88%; P = .0069). The disease control rate (68.63% vs. 49.10%, P = .044) of the TACE-LEN group was significantly higher. In the subgroup analysis, the OS of the TACE-LEN group was better than TACE-alone group in patients with Barcelona Clinic Liver Cancer stage C (1-year OS rate: 44.44% vs. 17.14%, 2-year OS rate: 8.67% vs. 0%; P = .009). Factor analysis concluded that serum alkaline phosphatase and treatment protocol (TACE-LEN vs. TACE) were independent influencing factors of OS. The most common treatment-related AEs included decreased albumin (n = 28, 54.9%), hypertension (n = 23, 45.1%), elevated aspartate transaminase (n = 21, 41.2%) and elevated total bilirubin (n = 18, 35.2%) in TACE-LEN group. Conclusion: Compared with TACE monotherapy, TACE combined with lenvatinib effectively prolonged the OS time with a controllable safety profile for patients with uHCC. Cite this article as: Zong Z, Tang R, Li M, et al. Efficiency and stability of transarterial chemoembolization combined with or without lenvatinib for unresectable hepatocellular carcinoma. Turk J Gastroenterol. 2024;35(3):212-222.